Recent advances in Bletilla striata polysaccharide research: extraction methodologies, structural elucidation, pharmacological mechanisms, structure–activity relationships, and therapeutic delivery applications - Wang, Bo; Wu, Chaomeng; Ma, Yingjuan; Liu, Xiaofen; Tao, Lijun; Zhou, Xuebing; Jia, Limin (Frontiers in Pharmacology, 2025)
Bletilla striata is a traditional Chinese medicine (TCM) used for hemostasis, detumescence, and tissue regeneration. Its major bioactive component, Bletilla striata polysaccharide (BSP), is a water-soluble heteropolysaccharide composed primarily of mannose and glucose. Various extraction techniques—including hot water, ultrasonic assisted, and microbial fermentation methods—have been developed to isolate BSPs, with extraction parameters significantly influencing its structural features. BSPs exhibit diverse pharmacological activities, such as wound healing, immunomodulation, anti-inflammatory, antioxidant, and gut microbiota regulatory effects. Despite extensive studies, the structure–activity relationships (SARs) and toxicological profile of BSPs remain incompletely understood. Owing to its favorable biodegradability and biocompatibility, BSPs show promise as a nanocarrier for drug delivery. This review summarizes advanced purification and structural characterization techniques, pharmacological mechanisms, potential toxicities, and drug delivery applications of BSPs, providing a translational framework for future research and development.